On the Design of a GaN-Based Solid-State Circuit Breaker for On-Board DC Microgrids - Symeon Fountoukidis; Nick Rigogiannis; Georgios Voltsis; Konstantinos Terzopoulos; Michael Loupis; Nikolaos Papanikolaou (Engineering Proceedings, 2024)
The concept of more electric aircraft (MEA) has gained popularity over the last few decades. As the power level of electric loads is constantly increasing, the installation of advanced protection systems becomes of paramount importance. In this context, this paper presents the design process and experimental validation of a solid-state circuit breaker (SSCB), utilizing gallium nitride (GaN) semiconductor switches, under various faulty conditions. In addition, a thermal analysis was carried out in the PLECS simulation platform to find the most appropriate design for the heat dissipation system. Experimental results on the developed GaN SSCB hardware prototype verify its functionality and good performance.